PENGUNDURAN DIRI RUSIA DARI ICC : TELAAH BERDASARKAN ASAS GOOD FAITH DALAM HUKUM PERJANJIAN INTERNASIONAL - Saragih, Jogi Talar (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This study aims to examine the validity of Russia's withdrawal from the International Criminal Court (ICC) in light of the principle of good faith as established in the Vienna Convention on the Law of Treaties (VCLT). The primary objectives of the research are, firstly, to elucidate the legal implications of the principle of good faith within the 1969 VCLT. Second, to apply this principle to evaluate Russia's withdrawal from the ICC in 2016. To address the legal questions raised by this research, both the statutory and conceptual approaches have been employed. The statutory approach refers to the 1969 VCLT as the source of statutory law, while the conceptual approach draws on the opinions of scholars regarding the application of the principle of good faith in international treaty law. The findings of this research indicate that Russia's withdrawal from the ICC is not legitimate, as it demonstrates Russia's intention to avoid the application of the ICC's provisions. This withdrawal constitutes an act of bad faith, as it deliberately circumvents the unfavorable provisions of the agreement that apply to Russia following its occupation of Crimean territory.